The Impact of Market Size and Composition on Health Insurance Premiums: Evidence from the First Year of the Affordable Care Act - Dickstein, Michael J.; Duggan, Mark; Orsini, Joe; Tebaldi, Pietro (American Economic Review, 2015)
Under the Affordable Care Act, individual states have discretion in how they define coverage regions, within which insurers must charge the same premium to buyers of the same age, family structure, and smoking status. We exploit variation in these definitions to investigate whether the size of the coverage region affects outcomes in the ACA marketplaces. We find large consequences for small and rural markets. When states combine small counties with neighboring urban areas into a single region, the included rural markets see 0.6 to 0.8 more active insurers, on average, and savings in annual premiums of between $200 and $300.